Differential response of open-pollinated and hybrid tomato varieties to PGPR inoculation under field condition - Delfin, Evelyn F.; Rodriguez, Felicito M.; Paterno, Erlinda S. (2011)
Enhancement of plant growth through inoculation with plant growth promoting rhizobacteria (PGPR) has been reported for various vegetable and agronomic crops. However, studies on varietal response to PGPR inoculation under field condition were limited. A field trial was conducted at UPLB to determine the response of ten open-pollinated (OP) and hybrid tomato varieties to PGPR inoculation under two levels of fertilization, recommended rate (138-47-60 NPK) and half the recommended rate. The following parameters were assessed at flowering and fruiting stage; plant growth, number of flower clusters and branches, nutrient uptake, dry matter and fruit yield. Inoculation increased the number of branches formed by Improved Apollo by 33% for both fertilizer rates while Rosanna had a remarkable 40% increase with half-fertilizer rate application. Inoculation also increased the number of flower clusters of Rossana by 60% in the half-fertilizer treatment while 60-150% increases were obtained for inoculated Caraibo, Discovery and Atlas with full fertilization. The increase in root dry weight due to inoculation also increased the root shoot ratio of OP varieties, Northern Red and Improved Apollo. In general, inoculation increased P content of the evaluated varieties from 0.20 to 0.21% P which also resulted to enhanced P uptake. The increase in P content of inoculated tomatoes indicates P solubilising activity of PGPR. With inoculation, the total fruit weight of Rosanna was increased by 27% while Atlas showed 19% increase across fertilizer treatments. The results showed the different responses of OP and hybrid tomatoes to PGPR inoculation. There were OP and hybrid tomatoes which responded positively to inoculation while there were varieties which did not show significant response. This variation needs to be verified under different field condition because a significant variety-PGPR interaction is crucial in the adoption of PGPR inoculation technology.
Keywords: Tomatoes; Phosphorus; Rhizobacteria